Optimal Bicelle Size q for Solution NMR Studies of the Protein Transmembrane Partition. Issue 6 (22nd December 2016) - Piai, Alessandro; Fu, Qingshan; Dev, Jyoti; Chou, James J.
Abstract: Structural characterization of transmembrane proteins in isotropic bicelles has become an increasingly popular application of solution NMR spectroscopy, as the fast‐tumbling bicelles are membrane‐like, yet can often yield spectral quality comparable to those of detergent micelles. While larger bicelles are closer to the true lipid bilayer, it remains unclear how large the bicelles need to be to allow accurate assessment of the protein transmembrane partition in the lipid bilayer. Here, we address the above question from the perspective of the protein residing in the bicelles, through systematic measurement of the protein chemical shift and transmembrane partition at different lipid/detergent ratios ( q ), ranging from 0.3 to 0.7, using the transmembrane domain of the human Fas receptor as model system. We found that the lipid environment of the bicelles, as reflected by the protein chemical shift, begins to be perturbed when q is reduced to below 0.6. We also implemented a solvent paramagnetic relaxation enhancement (PRE) approach for bicelles to show that the protein transmembrane partition in bicelles with q =0.5 and 0.7 are very similar, but at q =0.3 the solvent PRE profile is significantly different. Our data indicate that q values between 0.5 and 0.6 are a good compromise between high resolution NMR and closeness to the membrane environment, and allow accurate characterization of the protein position in the lipid bilayer. Abstract : A robust method is described to assess the optimal bicelle size(s) to accurately determine the position of oligomeric transmembrane protein domains in lipid bilayer. This method combines solvent paramagnetic agent titration and paramagnetic relaxation data fitting with sigmoid function. Our results show that bicelles with a lipid/detergent ratio ( q ) between 0.5 and 0.6 ensure an almost‐ideal lipid bilayer environment, while at the same time providing favorable relaxation properties that are compatible with high resolution NMR spectroscopy.